2012
DOI: 10.1002/cncr.27604
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise cumulation of RUNX3 methylation mediated by Helicobacter pylori infection contributes to gastric carcinoma progression

Abstract: BACKGROUND: Helicobacter pylori has been recognized as a definite carcinogen for gastric cancer (GC); however, the pathogenesis of H. pylori infection remains unclear. Runt-related transcription factor 3 (RUNX3) is a candidate tumor suppressor gene whose deficiency is causally related to GC. However, in H. pylori infection-associated GC, the role of RUNX3 has not been studied. METHODS: The authors used real-time methylation-specific polymerase chain reaction analysis to determine methylation status of the RUNX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 45 publications
1
74
0
1
Order By: Relevance
“…Consistent with previous findings, the present study demonstrated vimentin overexpression in GC cell lines and clinical GC tissues. Over the past decade, knowledge of the importance of epigenetic events in the control of normal cellular processes, and aberrant events leading to tumor development and progression has increased (3)(4)(5)(6)(7)22). DNA methylation is a major epigenetic mechanism that has been intensively investigated in the context of gene regulation and abnormal gene silencing in cancer cells (3)(4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with previous findings, the present study demonstrated vimentin overexpression in GC cell lines and clinical GC tissues. Over the past decade, knowledge of the importance of epigenetic events in the control of normal cellular processes, and aberrant events leading to tumor development and progression has increased (3)(4)(5)(6)(7)22). DNA methylation is a major epigenetic mechanism that has been intensively investigated in the context of gene regulation and abnormal gene silencing in cancer cells (3)(4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…Gastric tumorigenesis is a complex, multi-step process involving alterations of numerous genes (2). Aberrant promoter methylation is an important mechanism for silencing certain tumor suppressor and tumor-associated genes, and is significant during the pathogenesis and progression of certain types of human cancer (3,4), including GC (5,6). Data suggests that DNA methylation may be a useful biomarker for cancer risk evaluation (3,5), early diagnosis (5), prognosis (4,5) and evaluation of sensitivity to chemotherapy (7).…”
Section: Introductionmentioning
confidence: 99%
“…12 Several studies suggested RUNX-3 methylation as a risk factor for the gastric carcinogenesis in patients with H. pylori infection. 23,24 One study suggested that epigenetic events and gene methylation were not evenly distributed throughout the gastric mucosa, so multiple biopsies in different parts of stomach should be performed to determine methylation status. 8 In this study, one biopsy was used for methylation status, which might be a limitation.…”
Section: 18mentioning
confidence: 99%
“…A number of studies have showed that RUNX3 promoter region methylation affects its expression and plays an important role in the occurrence of early gastric cancer. Lu et al (2012) analyzed the methylation status of RUNX3 promoters in 220 samples of chronic atrophic gastritis, 196 samples of intestinal metaplasia, 134 samples of gastric adenoma, 102 samples of dysplasia, and 202 samples of gastric cancer with paired noncancerous mucosa tissues and corresponding blood specimens, and found that RUNX3 promoter methylation increased with progression of gastric mucosal lesions: the methylation rates were 15.9% in chronic atrophic gastritis, 36.7% in intestinal metaplasia, 41.8% in gastric adenoma, 54.9% in dysplasia and 75.2% in gastric cancer, indicating that circulating RUNX3 methylation was a valuable biomarker for the detection of early gastric cancer. found that the combined detection of RUNX3 gene methylation and serum CEA, CA19-9 showed higher sensitivity than CEA and CA19-9 combination in the diagnosis of gastric cancer, but no reduced specificity DOI:http://dx.doi.org/10.7314/APJCP.2013.14.6…”
Section: Runt-related Transcription Factor 3 (Runx3)mentioning
confidence: 99%